First-Principle Modelling of Forsterite Surface Properties: Accuracy of Methods and Basis Sets - Demichelis, Raffaella; Bruno, M.; Massaro, F.; Prencipe, M.; De La Pierre, Marco; Nestola, F. (Wiley, 2015)
The seven main crystal surfaces of forsterite (Mg2SiO4) were modeled using various Gaussian-type basis sets, and several formulations for the exchange-correlation functional within the density functional theory (DFT). The recently developed pob-TZVP basis set provides the best results for all properties that are strongly dependent on the accuracy of the wavefunction. Convergence on the structure and on the basis set superposition error-corrected surface energy can be reached also with poorer basis sets. The effect of adopting different DFT functionals was assessed. All functionals give the same stability order for the various surfaces. Surfaces do not exhibit any major structural differences when optimized with different functionals, except for higher energy orientations where major rearrangements occur around the Mg sites at the surface or subsurface. When dispersions are not accounted for, all functionals provide similar surface energies. The inclusion of empirical dispersions raises the energy of all surfaces by a nearly systematic value proportional to the scaling factor s of the dispersion formulation. An estimation for the surface energy is provided through adopting C6 coefficients that are more suitable than the standard ones to describe O[BOND]O interactions in minerals. A 2 × 2 supercell of the most stable surface (010) was optimized. No surface reconstruction was observed. The resulting structure and surface energy show no difference with respect to those obtained when using the primitive cell. This result validates the (010) surface model here adopted, that will serve as a reference for future studies on adsorption and reactivity of water and carbon dioxide at this interface.